User perceptions of intelligent offloading diabetic footwear - Hemler, Sarah L.; Sommerich, Carolyn M.; Correia, Jorge C.; Pataky, Zoltan (Frontiers in Endocrinology, 2024)
Aims: Adherence to therapeutic footwear is vital for effective diabetic foot ulcer prevention and treatment. Understanding the key adherence factors and potential barriers is important for footwear design and implementation. Our team is creating intelligent offloading footwear to prevent lower extremity amputations in people living with diabetes (PLwD). This exploratory study assessed the ability of the established Unified Theory of Acceptance and Use of Technology (UTAUT) model to predict behavioral intention to use or recommend this intelligent offloading footwear by PLwD, caregivers of PLwD, or medical professionals treating of PLwD. Methods: Online and paper questionnaires were implemented to assess the impact of the UTAUT model factors (performance expectancy, effort expectancy, social influence, facilitating conditions) and psychosocial factors (attitude, anxiety, self-efficacy) on the overall behavioral intention to use the footwear. Furthermore, factors influencing potential acceptance and rejection of the footwear were explored. Results: Both patients (4.0/5) and medical professionals (4.1/5) showed a behavioral intention to "agree" to use or recommend the footwear when it becomes available. Structural equation modeling showed that the UTAUTis constructed model may not be the best indicator for behavioral intention here based on a lack of statistical significance. However, the logistic regression modeling showed that the social influence for PLwD (p=0.004) and the attitude toward the footwear for medical professionals (p=0.001) may be the most important when designing and implementing the footwear, though several other factors (performance expectancy, effort expectancy, facilitating conditions, and self-efficacy) were also important for one or both of these populations. Additionally, cost and clinician support were shown to be important factors influencing potential acceptance of the footwear.